A framework for integrating ecosystem services as endpoint impacts in life cycle assessment. (10th October 2022) - Hardaker, Ashley; Styles, David; Williams, Prysor; Chadwick, Dave; Dandy, Norman
Abstract: Life cycle assessment is an analysis technique used to assess the environmental burdens of products or production processes. Ecosystem services is a concept used to understand the ways functioning ecosystems support human wellbeing. Both are used to understand how anthropogenic pressures impact the environment. The integration of ecosystem services as indicators in life cycle assessment is increasingly being explored, however there are several limitations with current frameworks. A brief review of existing approaches found they incorporate ecosystem services as midpoint indicators within traditional life cycle assessment structures and aggregate these impacts under the conventional 'areas of protection' (i.e., groupings of impacts). These approaches typically only focus on how product systems negatively affect ecosystem service supply (predominantly through land use) and overlook how product systems use up ecosystem services to mitigate their emissions or how interventions in product systems could improve ecosystem service supply. It is argued by several authors that ecosystem services are better placed as endpoint indicators representing damage to the instrumental value of ecosystems in a manner distinct to existing life cycle assessment impact categories, so that any changes in their delivery should be assessed within a new area of protection. In this paper, the potential for an ecosystem services area of protection within life cycle assessment is explored and a novel framework for modelling endpoint characterisation factors related to ecosystem service impacts that addresses the limitations of existing approaches is presented. The proposed novel framework respects existing life cycle assessment protocols by quantifying the endpoint damage to ecosystem services from product systems alongside existing methodologies for modelling endpoint impacts to ecosystem quality (biodiversity), human health and natural resources. This approach, based on small number of pertinent end-point indicators, has potential to broaden out LCA assessments of product systems and quantify the multiple ways they impact ecosystem services. Highlights: Presents framework for integrating ecosystem services in life cycle assessment. Novel method for generating characterisation factors for ecosystem service impacts. Ecosystem services are included as endpoints within further area of protection. Framework allows multiple impacts of product systems on ecosystem services to be assessed. Improves representation of ecosystem service impacts beyond land use.